PERANCANGAN PROTOTYPE PENJEJAK CAHAYA MATAHARI PADA APLIKASI PEMBANGKIT LISTRIK TENAGA SURYA - Hendry Eko Hardianto; Reza Satria Rinaldi (Foristek, 2012)
Solar energy is one of the alternative energy sources which can be used as electrical energy. As the effect of earth rotation and revolution, it had not been optimized maximally yet. The rotation of earth causes the sun moves from east to west every day, and the revolution of earth causes the sun move from north to south every year. These phenomenons cause the differentintensity of sun light in every earth surface. To optimize the sun light, the design and realization of solar tracker is very important. The solar tracker has to be able to track the position of the sun and move the solar cell to face the sun light. The solar tracker can move in two axis with moving type of rotate and tilt, so it works optimally every time. This solar tracker is designed by using photo diode as light sensor and servo motor as actuator. The system uses ATMega8535 as control unit which able to process signal from the sensor and resulted Pulse Width Modulation to control servo motor moving. The testing showed this solar tracker capable to raise the average power to 0.676 watt and the eficiency to 36,216%. The error of tracking is 90at heavy cloud.